Equality and Bhakti Movement in India: Challenging Caste: Equality and Social Reform in the Bhakti Movement of India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Bhakti Movement originated in India as a reaction against the caste system and ritualism. It was started by the Vaishnava and Saiva saints of south India. It attacked the caste system and preached equality of all people by emphasising over the doctrine that there is only one God and all people are equal in the eyes of God. The teachings of bhakti saints like Guru Nanak, Kabir and Ravidas helped in reforming the Indian society. They tried to evolve a new social order by following the principles of equality and by denouncing caste distinction.